Convenient synthesis of α,β-unsaturated γ-butyrolactones and γ-butyrolactams via decarboxylative iodination of paraconic acids and β-carboxyl-γ-butyrolactams using 1,3-diiodo-5,5-dimethylhydantoin - Supasorn Phae-Nok (2018)
© 2015 The Royal Society of Chemistry. A convenient synthetic approach to α,β-unsaturated γ-butyrolactones and α,β-unsaturated γ-butyrolactams is developed. The reaction proceeds via decarboxylative iodination of paraconic acids and β-carboxyl-γ-butyrolactams, employing 1,3-diiodo-5,5-dimethylhydantoin (DIH) under irradiation, followed by dehydroiodination of β-iodo-γ-butyrolactones and γ-butyrolactams providing good yields of α,β-unsaturated γ-butyrolactones and γ-butyrolactams, which are synthetically useful building blocks in organic synthesis.